Pengelolaan Kota Kreatif Berbasis Lingkungan Berkelanjutan di Kota Padang Melalui Analisis PLS-SEM dengan STATA - Haris Satria; Eri Barlian; Heldi (Journal of Social and Policy Issues, 2023)
This study aims to analyze the creative city management system and the factors that influence the development of creative cities. This study uses mixed methods to develop, produce, and test product validity at the top level of management. This research involved 52 respondents consisting of academics, businessmen, government officials, media, and aggregators as multistakeholder representatives (Hexa-Helix) in Padang. Measurement analysis study using PLS-SEM with STATA. The results of the study show that Padang has the potential to develop through optimizing a sustainable, environmentally-based, creative city management system. The goodness of fit test shows a R-squared of 0.972, and it can be said that the model is very good because it fulfills the good fit model indicator with a value close to 1 based on the SEM parameters. The conclusion is that creative cities are influenced by human resources in multi-stakeholder synergy and human resources (HR) formed with the hexa helix can influence the development of creative cities.